Antibiotic contaminants and their impact in Gingee River, Puducherry: Insights from SPE-UPLC-MS/MS and zebrafish study - Gokul P.; Sobanaa M.; Hari Krishna Kumar S.; Prathiviraj R.; Pamanji R.; Suseela M.N.L.; Vallamkonda B.; Setia A.; Selvin J.; Muthu M.S. (My University, 2025)
The accumulation of antibiotic residues in ecosystems is intricately tied to the proliferation of bacterial resistance to antibiotics, with far-reaching consequences for the health and welfare of both humans and animal well-being. The analytical approach integrates solid phase extraction (SPE) with ultra performance liquid chromatography-mass spectrometry (UPLC-MS/MS) for quantification of multiclass antibiotic residues. Upon applying the aforementioned method to analyse water samples collected from the Gingee River, revealed the existence of five distinct antibiotics. This is the first study reporting antibiotic concentration in the Gingee River, Puducherry. The concentrations of nalidixic acid, sulfamethoxazole, and tetracycline were determined to be 8.5, 6.9, and 4.8 μg/L, respectively. Metronidazole and trimethoprim were detected at concentrations below the quantifiable limit. The microbial study of water samples also indicated that Shigella sp. and Acinetobacter sp. were the most predominant bacterial species present. Our preliminary observation underscores the importance of comprehending the intricate relationship between the presence of antibiotics in water and the concurrent proliferation of antibiotic-resistant bacteria within bacterial populations in the Gingee River. Further, we evaluated the developmental toxicity of environmentally relevant concentrations of antibiotics in zebrafish. The zebrafish model confirms that these antibiotics are sublethally hazardous to human health at environmentally relevant concentrations. This integrated approach allows unique views on the environmental impact of antibiotic residues, their role in the evolution of antibiotic resistance, and their impact on human health. © 2024 The Author(s). Published by Oxford University Press. All rights reserved.